The Effectiveness of Combination of Benson Relaxation Techniques and Kitaro Instrumental Music on Risk Behavior of Violent Patients - Mira Santika; Betie Febriana; Wigyo Susanto (Universitas Islam Sultan Agung, 2023)
Violent behavior problems are often mental health problems. The total number of mental patients in 2013-2019 was 3914, with 39.2% (1534) representing problems of violent behavior, and this number ranked second in the nursing problems experienced by patients. One of the treatments offered to patients with violent behavior is relaxation and music skills. Relaxation actions affect alternatives that give patients calm, comfort, and relaxation, and reduce emotion. This research is a Quasi Esperiment study, in the control and treatment groups, using a total sampling technique with 30 respondents. Data collection using a questionnaire. Data analysis techniques used the Margin Homogeneous Paired Margin Test and the Non-Paired Mann Withney. Marginal Homogenotas Test Paired and Mann Withney Unpaired obtained results that the value of p is 0.02 (p